Use of Techniques and Tools for Investigative Process in Computational Forensic Expertise - Priscilla Leao De Lima (Global Journal of Computer Science and Technology, 2022)
Computer forensics investigates and retrieves information about a fact, as well as examining digital evidence that can be decisive in any technological situation. The research will explain techniques that are used during the expertise, ensuring the integrity of the data so that the analysis is not impaired. First, a bibliographic survey will be carried out in search of concepts about data collection and analysis techniques in the forensic area. The method includes performing procedures such as equipment identification and chain of custody in a simulated environment, in order to determine the best mechanism for the presented scenario. Finally, the main steps and forensic tools were presented for a better way in which the expert can use to perform the exact analysis of the crime.